Influence of MHD flow on forced convection in a saturated porous duct with ohmic heating - Rajapriyanka Eswaran; M. S. Jagadeesh Kumar (Discover Applied Sciences)
Abstract This study investigates the forced convective flow in a horizontally extended parallel-plate channel filled with a sparsely packed, chemically inert porous medium under magnetohydrodynamic (MHD) effects. Utilizing the Forchheimer model to account for both viscous and inertial effects, the problem is formulated as a nonlinear boundary value problem and solved using the Differential Transformation Method (DTM). The key observations indicate that as the Darcy number increases, there is a decrease in flow velocity, eventually transitioning to plug flow at higher values. To investigate thermal characteristics, uniform Ohmic heating is employed, and the temperature distribution is determined using the steady-state thermal energy equation, which excludes axial conduction. The findings demonstrate that both the Darcy number and magnetohydrodynamic (MHD) effects have a substantial impact on the velocity and temperature profiles. The DTM solutions are validated against limiting cases in the literature and demonstrated good agreement. This study enhances the understanding of porous media and the effects of MHD on convective flow and thermal distribution, providing valuable insights for applications involving porous structures and electromagnetic fields.